Don't make cancer survivors pay twice—the right for them to be "forgotten" should be law everywhere. (21st September 2022) - Lawler, Mark; Meunier, Françoise
Abstract : We need laws that empower cancer survivors to live without the stress of financial toxicity, say Mark Lawler and Françoise Meunier